An introduction to soil reinforcement and geosynthetics - Babu, G L Sivakumar (Universities Press, 2006)
An introduction to soil reinforcement and geosynthetics / Babu, G L Sivakumar. -- Kolkata: Universities Press, 2006 624.15136 B115 No. of Copies : 1